2022
DOI: 10.1097/md.0000000000028853
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of patients with carnitine deficiency or a defect of the fatty acid β-oxidation pathway

Abstract: Carnitine is essential for the transport of long-chain fatty acids from the cytoplasm to the mitochondrial matrix. The carnitine shuttle transports long-chain fatty acylcarnitine to the mitochondrial matrix. Subsequently, long-chain fatty acyl CoA, which is split from long-chain fatty acylcarnitine by carnitine palmitoyltransferase II, undergoes fatty acid β-oxidation. Acetyl CoA is produced from long-chain fatty acyl CoA via fatty acid β-oxidation and aids in the synthesis of adenosine triphosphate via the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The origin of human FAs includes three metabolic pathways; de novo synthesis of FAs, exogenous FA uptake, and degradation of FAO. The de novo synthesis of FAs relies on enzymes such as ATP citrate lyase (ACLY), acetyl‐CoA carboxylase (ACC), FA synthase (FASN), and stearoyl‐CoA desaturase (SCD) 15 . However, in CRC cells, FASN, SCD, ACLY, and the key enzyme carnitine palmitoyltransferase (CPT1) in the FAO process are all upregulated, thereby promoting the production of FAs to provide the material basis for the growth of CRC cells 16 .…”
Section: Reprogramming Of Lipid Metabolism In Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of human FAs includes three metabolic pathways; de novo synthesis of FAs, exogenous FA uptake, and degradation of FAO. The de novo synthesis of FAs relies on enzymes such as ATP citrate lyase (ACLY), acetyl‐CoA carboxylase (ACC), FA synthase (FASN), and stearoyl‐CoA desaturase (SCD) 15 . However, in CRC cells, FASN, SCD, ACLY, and the key enzyme carnitine palmitoyltransferase (CPT1) in the FAO process are all upregulated, thereby promoting the production of FAs to provide the material basis for the growth of CRC cells 16 .…”
Section: Reprogramming Of Lipid Metabolism In Crcmentioning
confidence: 99%
“…The de novo synthesis of FAs relies on enzymes such as ATP citrate lyase (ACLY), acetyl-CoA carboxylase (ACC), FA synthase (FASN), and stearoyl-CoA desaturase (SCD). 15 However, in CRC cells, FASN, SCD, ACLY, and the key enzyme carnitine palmitoyltransferase (CPT1) in the FAO process are all upregulated, thereby promoting the production of FAs to provide the material basis for the growth of CRC cells. 16 Furthermore, when the expression of FA de novo synthase (FASN) is inhibited, it was surprisingly found that CRC cells still grew at a non-attenuating rate due to intake of exogenous FAs that ensured their survival.…”
Section: Reprogramming Of Lipid Metabolism In Crcmentioning
confidence: 99%
“…However, currently, LE is additionally used as solvent of propofol and etomidate, and treatment of drug toxicity including LAST. Long-chain fatty acid is transported to cardiac mitochondria from cytoplasm using following three steps, and subsequently used to produce adenosine triphosphate (ATP) [7]. Long-chain fatty acyl-CoA is produced from long-chain fatty acid by long-chain fatty acyl-CoA synthase in cytoplasm [7].…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain fatty acid is transported to cardiac mitochondria from cytoplasm using following three steps, and subsequently used to produce adenosine triphosphate (ATP) [7]. Long-chain fatty acyl-CoA is produced from long-chain fatty acid by long-chain fatty acyl-CoA synthase in cytoplasm [7]. First, This article is protected by copyright of Korean Journal of Anesthesiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation